Exploration of current challenges in rehabilitation from the perspective of healthcare professionals: Switzerland as a case in point. Issue 3 (March 2022) - Spiess, Adrian Andrea Flavio; Skempes, Dimitrios; Bickenbach, Jerome; Stucki, Gerold
Highlights: Rehabilitation professionals identified and prioritized critical issues in rehabilitation-services in Switzerland. HIC and LMIC face similar challenges in strengthening rehabilitation. Rehabilitation-specific education and training must be improved. The financing of rehabilitation must set incentives for improved quality and performance. Issues pertaining to service planning and delivery require immediate policy attention. Abstract: Rehabilitation is a health strategy with the potential to mitigate the negative health consequences of population ageing and the rise of noncommunicable diseases. Literature indicates that even in high-income countries rehabilitation services can be improved. The purpose of this study is to engage rehabilitation professionals in Switzerland in identifying and prioritizing current challenges in the development and delivery of rehabilitation services. We conducted a qualitative study consisting of interviews with key informants and a stakeholder consultation. Thirteen interviews were conducted and analysed using inductive thematic analysis. Identified challenges were refined, extended, and prioritized through multi-voting in a workshop attended by a wide range of rehabilitation professional organizations. Final results were subject to further analysis and member checking. We identified nineteen challenges, of which eight were viewed as highly important. Results suggest the need to revise the financing system for rehabilitation services, highlighted a poor integration of rehabilitation in primary care, a lack of academic rehabilitation training, and insufficient funding for research. Finally, we identified a perceived lack of awareness for rehabilitation among policy-makers and the public. This study provides a unique perspective on challenges in rehabilitation practice and policy and offers an opportunity for professionals, policy-makers, and other stakeholders, to influence and guide the rehabilitation service agenda both in Switzerland and in terms of mutual learning also in other countries.